Application of Deep Sea Water for Multi-Trusses Cultivation of Tomato Using A Nutrient Film Technique - YUDI CHADIRIN; TAKAHISA MATSUOKA; HERRY SUHARDIYANTO (Bogor Agricultural University, Indonesia, 2008)
Deep sea water (DSW) that was applied to 3 trusses of cultivated tomato for 2 weeks affected fruits properties. However, advantageous effects on the soluble solids content, acidity, and dry matter content of the fruit tend to decline from 1st truss to the successive trusses. Thus it is necessary to study the effect of DSW application when it is applied for longer than 2 weeks in cultivated multi-trusses. In this study, DSW treatment was applied for different durations to obtain effect on fruits development and fruit properties of the 1st to 3rd truss in a 3 truss tomato cultivation system using a nutrient film technique. The results of the study show that DSW treatment has strong effect on fruit enlargement during the stage of rapid fruit growth, which lasts until the fruit almost reaches the final size. Treated plants produced tomatoes with better organoleptic with higher soluble solids content and higher acidity, higher dry matter content, a thicker and more resistant cuticle and also gave higher yields (weight and no of fruits) than in single truss tomato cultivation. Key words: tomato (Lycopersicon esculentum), deep sea water, fruit development, fruit properties, multi-trusses cultivation, nutrient film technique